Prevejanje ! veljavnosti Zaritovega vprašalnika za oceno obremenjenosti skrbnikov v slovenskem jeziku - Adlešič, Barbara (Rehabilitacija (Ljubljana), 2020)
Background: Caregiving for patients with chronical illness has adverse effects on the caregiver's own physical and mental health. The Zarit Burden interview (ZBI) is the most widely used instrument for assessing family caregiving burden. The aim of this study was to evaluate the psychometric properties of the Slovenian version of the ZBI in caregivers of stroke survivors. Methods: Data were collected from 34 pairs of primary informal caregivers and stroke patients at least one year after stroke who had their checkup from 1 August 2017 to 17 October 2017 at the Outpatient clinic for rehabilitation of patients after stroke, who live at home and have had hospital rehabilitation at the University Rehabilitation Institute in Ljubljana. We excluded caregivers with depression or paid caregivers. Caregivers completed the questionnaire which consisted of socio-demographic questions and the ZBI translated into Slovenian language. Internal consistency of the ZBI was assessed using Cronbach coefficient. Results: Almost half (47 %) of caregivers reported minimal burden and 41 % mild to moderate burden. The internal consistency was high (% = 0,87). The mean ZBI score was 23.7 (SD 11.9). Low item-total correlation was observed for the items 13, 4, 20 and 21, and high for the items 2, 10 and 14. Conclusion: The Slovenian version of the ZBI has high validity and is useful as complementary instrument for measuring the burden of caregivers in clinical contexts. Future studies could lead to a better understanding of caregiver burden in different chronical illnesses. Further, with appropriate intervention, we could improve the family's and patient's quality of life.
Keywords: burden; caregivers; Carevigers; Interviews as Topic; možganska kap; obremenjenost; psihometrične lastnosti; psychometric characteristics; skrbniki; stroke; Validation Studies as Topic; Zarit Burden Interview; Zaritov vprašalnik obremenjenosti skrbnikov